Creatine supplementation and exercise performance: an update - Williams, M. H.; Branch, J. D. (Journal of the American College of Nutrition, 1998)
Creatine, a natural nutrient found in animal foods, is alleged to be an effective nutritional ergogenic aid to enhance sport or exercise performance. Research suggests that oral creatine monohydrate supplementation may increase total muscle creatine [TCr], including both free creatine [FCr] and phosphocreatine [PCr]. Some, but not all, studies suggest that creatine supplementation may enhance performance in high-intensity, short-term exercise tasks that are dependent primarily on PCr (i.e., < 30 seconds), particularly laboratory tests involving repeated exercise bouts with limited recovery time between repetitions; additional corroborative research is needed regarding its ergogenic potential in actual field exercise performance tasks dependent on PCr. Creatine supplementation has not consistently been shown to enhance performance in exercise tasks dependent on anaerobic glycolysis, but additional laboratory and field research is merited. Additionally, creatine supplementation has not been shown to enhance performance in exercise tasks dependent on aerobic glycolysis, but additional research is warranted, particularly on the effect of chronic supplementation as an aid to training for improvement in competitive performance. Short-term creatine supplementation appears to increase body mass in males, although the initial increase is most likely water. Chronic creatine supplementation, in conjunction with physical training involving resistance exercise, may increase lean body mass. However, confirmatory research data are needed. Creatine supplementation up to 8 weeks has not been associated with major health risks, but the safety of more prolonged creatine supplementation has not been established. Creatine is currently legal and its use by athletes is not construed as doping.